Effect of whey protein supplementation combined with resistance training on body composition, muscular strength, functional capacity, and plasma-metabolism biomarkers in older women with sarcopenic obesity: A randomized, double-blind, placebo-controlled trial - Nabuco, Hellen C.G.; Tomeleri, Crisieli M.; Fernandes, Rodrigo R.; Sugihara Junior, Paulo; Cavalcante, Edilaine F.; Cunha, Paolo M.; Antunes, Melissa; Nunes, João Pedro; Venturini, Danielle; Barbosa, Décio S.; Burini, Roberto Carlos [UNESP]; Silva, Analiza M.; et al. (Elsevier, 2019)
Backgrounds & aims: Obesity and sarcopenia are independent illnesses associated with contemporary dietary and physical activity behaviors, aggravated by aging. Their coexistence is termed sarcopenic obesity (SO). Hence, increasing protein intake and resistance training (RT) are interventions that could counteract these illnesses. The objective of this investigation was to analyze the effects of whey protein (WP) supplementation associated with RT on body composition, muscular strength, functional capacity, and plasma-metabolism biomarkers in older women with SO. Methods: Twenty six sarcopenic (appendicular lean soft tissue ALST < 15.02 kg) obese (body fat mass ≥ 35%) older women were randomly assigned to receive daily, either 35 g of WP (WP group) or placebo (PLA group), combined with supervised RT (8 exercises, 3 × 8–12 rep, 3 times a week), during a 12-week protocol. Blood samples, blood pressure, dietary intake, functional capacity tests, the one repetition maximum (1RM) test, and body composition were assessed before and after the intervention period. Two-way analysis of variance for repeated measures was applied for comparisons. Results: The WP group presented greater (P < 0.05) increases in ALST (WP = 6.0% vs. PLA = 2.5%) and decreases in (P < 0.05) total (−3.3% vs. −0.3%) and trunk fat mass (WP = −5.1% vs. PLA = −1.1) and IL-6 (WP = −34.6% vs. PLA = 9.3%) compared with the PLA group. Both groups demonstrated improved (P < 0.05) scores for muscular strength, waist–hip ratio, functional capacity, and other plasma-metabolism biomarkers without significant differences between conditions. Conclusion: Whey protein combined with RT increased ALST, and decreased total and trunk fat mass, improving sarcopenia and decreasing SO in older women, with a limited impact on inflammation. Registered under ClinicalTrials.gov Identifier n° NCT03752359.
Keywords: IL-6; Lean tissue; Obesity; Protein intake; Sarcopenia